2016
DOI: 10.1186/s40508-016-0056-7
|View full text |Cite
|
Sign up to set email alerts
|

The influence of storage time on relevant product properties of rubber seeds, rubber seed oil and rubber seed oil ethyl esters

Abstract: Background: Rubber seed oil (RSO) derived from rubber seeds is considered a promising plant oil. However, subsequent biodiesel synthesis from RSO was reported to be difficult due to the high acidity of the oil. Detailed studies on the effects of storage time of rubber seeds on relevant product properties such as acid value are not yet available. The authors here report a study on the influence of storage time on the moisture content of rubber seeds and the acid value of the oil within the seeds. In addition, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
4
6
0
Order By: Relevance
“…Shell and kernel represent 47.5% w/w db and 52.3% w/w db of the whole seed, respectively, showing a low data variation among the tested varieties. The obtained results are in line with literature [2,13,31]. Table 3 reports characterization results for kernel, shell and capsule.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Shell and kernel represent 47.5% w/w db and 52.3% w/w db of the whole seed, respectively, showing a low data variation among the tested varieties. The obtained results are in line with literature [2,13,31]. Table 3 reports characterization results for kernel, shell and capsule.…”
Section: Resultssupporting
confidence: 90%
“…Different authors have found low ash and moisture contents for the shell fraction [10,26,31]. The results obtained from characterization analysis show negligible differences among varieties, suggesting a quite standardized feedstock.…”
Section: Resultsmentioning
confidence: 90%
“…This may be due to the antioxidant in the formulation such as vitamin E and ascorbyl palmitate 21, which delayed the oxidation in the product. Also, the process of drying rubber seed before oil extraction helped the oil have good stability for long time storage 28 .…”
Section: Oxidative Stability Of Rubber Seed Cleansingmentioning
confidence: 99%
“…When assuming a 98 mol% biodiesel yield from RSO in combination with a molecular weight of 0.890 kg/mol and 0.298 kg/mol for RSO and RSO methyl esters [8], respectively, the estimated production scale of the biodiesel unit is approximately 15 kg/h, which is equivalent to 55 ton/y biodiesel (12 h operation per day for 306 days per year). An overview of the biodiesel process is presented in Fig.…”
Section: B Small Scale Biodiesel Production Using Cccs Technology 1)mentioning
confidence: 99%
“…By assuming the given composition and a rubber seed yield in the range of 100-1200 kg/(ha.y), the productivity of rubber seed oil (RSO) yield is estimated to be in the range 5-300 kg/(ha.y). The oil is a valuable source for the production of biodiesel (and by-product glycerol) and biopolymers [8], [9]. The protein rich press cake may find applications as a valuable source of protein [10], for instance to be used as cattle feed.…”
Section: Introductionmentioning
confidence: 99%